2021
DOI: 10.1037/pap0000373
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the sense of identity between men with alcohol use disorder, drug use disorder, and control group.

Abstract: The research on nonclinical samples reports the effect of a weak sense of identity on the use of psychoactive substances, but there has been no research to date on sense of identity in individuals with substance use disorder. The aim of the study was to test differences in sense of identity (SoI) in male patients with alcohol use disorder (AUD; n = 95) and drug use disorder (DUD; n = 95), and men without substance use disorder (SUD; n = 87). Participants (N = 277) completed the Multidimensional Identity Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
2
1
0
3
Order By: Relevance
“…Some clinicians have suggested that identity deficits are a common problem in individuals with AUD (Flores, 2004; Kohut, 1977; Levin, 1991). These clinical observations were supported by the report by Wojtynkiewicz et al (2021) who showed that male patients with AUD had a weaker sense of identity than male controls. It seems that the lack of a sense of security in close relationships and of a clear and stable sense of self can motivate various maladaptive behaviours, including excessive alcohol consumption, as a means of escaping the discomfort associated with insecurity and the lack of a coherent and positive self‐concept (Corte & Zucker, 2008).…”
Section: Introductionsupporting
confidence: 74%
“…Some clinicians have suggested that identity deficits are a common problem in individuals with AUD (Flores, 2004; Kohut, 1977; Levin, 1991). These clinical observations were supported by the report by Wojtynkiewicz et al (2021) who showed that male patients with AUD had a weaker sense of identity than male controls. It seems that the lack of a sense of security in close relationships and of a clear and stable sense of self can motivate various maladaptive behaviours, including excessive alcohol consumption, as a means of escaping the discomfort associated with insecurity and the lack of a coherent and positive self‐concept (Corte & Zucker, 2008).…”
Section: Introductionsupporting
confidence: 74%
“…In recent years, researchers have begun to focus on the development of the sense of self in individuals with substance use disorder (SUD) and its relationship with early adverse experiences. Wojtynkiewicz et al (2021) confirmed that individuals with SUD exhibited lower levels of self-identity than the control group. Furthermore, a study conducted on individuals with SUD demonstrated a negative association between insecure attachment and individual self-identity ( Wojtynkiewicz and Sekowski, 2022 ).…”
Section: Introductionsupporting
confidence: 53%
“…People with a consolidated identity consume significantly less alcohol; they also demonstrate psychological well-being and higher self-esteem as well as lower level of anxiety and depression [10,11]. Patients with AUD, as shown by research results [12], are characterised by greater identity deficits in terms of its lower coherence and stability and have less access to its content compared to those without AUD; also their identity is not related to the abstinence [12] or AUD [13] duration.…”
Section: ■ Wprowadzeniementioning
confidence: 99%
“…Osoby cechujące się skonsolidowaną tożsamością spożywają istotnie mniej alkoholu, a także przejawiają psychiczny dobrostan i wyższe poczucie własnej wartości oraz mniejsze nasilenie lęku i depresji [10,11]. Osoby uzależnione od alkoholu, jak wskazują wyniki badań [12], charakteryzują się większymi deficytami w zakresie tożsamości: mniejszą jej spójnością i stabilnością oraz mają mniejszy dostęp do jej treści w porównaniu z osobami nieuzależnionymi, a ich tożsamość nie wykazuje związku ani z czasem trwania abstynencji [12], ani uzależnienia [13].…”
Section: ■ Wprowadzenieunclassified
See 1 more Smart Citation